Uptake and utilization efficiency of nitrogen and phosphorus in barley genotypes - Svetla KOSTADINOVA; Nevenka GANUSHEVA; Marina MARCHEVA (Journal of Central European Agriculture, 2016)
Field experiment was carried out in order to study the genotypic variation in nitrogen and phosphorus uptake and utilization by barley. The study included nine Bulgarian genotypes of two-rowed barley: three cultivars Krami, Krasen, Kristi and six perspectives breading lines. The genotypes were sown in a randomized, complete block design with four replications after maize as predecessor with the size of experimental plots of 7 m2. It was found that barley genotypes differed in the uptake efficiency of both elements - nitrogen and phosphorus. Genotypes were divided into two groups in regard to nitrogen. Cultivars Krami, Krasen, Kristi and lines 2390300, 24102400, 22506999 uptake 170-186 kg N*ha-1, and lines 704112296, 24201900, 689069970 demonstrated higher nitrogen uptake efficiency 213-241 kg N*ha-1. Most of the new lines had higher phosphorus uptake efficiency in a range 90-111 kg Р2О5 ha-1compared to the varieties. The ratio total N/total Р2О5 uptake was close to 2.0 for the most of genotypes. The obtained mean values of nitrogen utilization efficiency were 81.6 kg biomass and 34.0 kg grain per kg N, respectively. The mean values of phosphorus utilization efficiency were 171.3 kg biomass and 71.4 kg grain per kg P2O5, respectively. The barley genotypes utilized more efficient phosphorus then total uptake nitrogen for producing grain and straw. Line 24102400 demonstrated higher nitrogen utilization efficiency for biomass and grain from all studied genotypes, followed by variety Krami. These two genotypes could be recommended as perspective in future improves of nitrogen efficiency in barley. Uptake efficiency of nitrogen and phosphorus positively correlated with the barley productivity and nutrients content in the grain and straw. In contrast, the relationship between total uptake of both elements at maturity and utilization efficiency of nitrogen or phosphorus for grain formation was negative.